Restrictions to Pharmacy Ownership and Vertical Integration in Estonia-Perception of Different Stakeholders - Marit Gross; Daisy Volmer (MDPI AG, 2016)
Objectives: From 2020, the ownership of community pharmacies in Estonia will be limited to the pharmacy profession, and the vertical integration of wholesale companies and community pharmacies will not be allowed. The aim of this study was to evaluate the perception of different stakeholders in primary healthcare toward the new regulations of the community pharmacy sector in Estonia. Methods: A qualitative electronic survey was distributed to the main stakeholders in primary healthcare and higher education institutions providing pharmacy education (n = 40) in May 2015. For data analysis, the systematic text condensation method was used. Results: The study participants described two opposing positions regarding the development of community pharmacies in the future. Reform supporters emphasized increased professional independence and more healthcare-oriented operation of community pharmacies. Reform opponents argued against these ideas as community pharmacists do not have sufficient practical experience and finances to ensure sustainable development of the community pharmacy sector in Estonia. Conclusion: Based on the current perception of all respondents, the future operation of the community pharmacy sector in Estonia is unclear and there is urgent need for implementation criteria for the new regulations.